ECOLOGICAL AND GEOGRAPHICAL PRECONDITIONS FOR THE EXISTENCE OF WILD ANIMALS AND THE CURRENT STATE OF HUNTING MANAGEMENT IN VOLYN REGION - Мисковець, Ірина; Андрощук, Ігор (SWorldJournal, 2026)
Hunting management is an important component of environmentally balanced natural resource use, as it is directly related to the condition of natural ecosystems, the level of biodiversity conservation, and the sustainability of wild animal populations. Un